2021
DOI: 10.1111/1740-9713.01554
|View full text |Cite
|
Sign up to set email alerts
|

Statisticians, Roll Up Your Sleeves! There's A Crisis to be Solved

Abstract: Statisticians play a key role in almost all scientific research. As such, they may be key to solving the reproducibility crisis. Heidi Seibold, Alethea Charlton, Anne‐Laure Boulesteix and Sabine Hoffmann urge statisticians to take an active role in promoting more credible science

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…is by no means a caricature, but a relatively accurate portrait of how studies in evolutionary biology are at present conducted and reported. The vast majority of investigations in our field still follow the traditional NHST scheme, despite ample exposure of its problems for about a century (Amrhein et al, 2017;Berkson, 1938;Boring, 1919;Gigerenzer, 2018;Greenland, 2017;Hurlbert & Lombardi, 2009;Johnson, 1999;Mayo, 2018;McShane et al, 2019;Oakes, 1986;Rozeboom, 1960;Szucs & Ioannidis, 2017;Yates, 1951;Ziliak & McCloskey, 2008), and despite broad agreement within the community of statisticians that the current state of NHST usage is damaging to science (Amrhein et al, 2019a;Benjamin et al, 2018;Seibold et al, 2021;Wasserstein & Lazar, 2016;Wasserstein et al, 2019).…”
Section: How Widely Are the Above Miscon Cep Ti On S Recog Nized In O...mentioning
confidence: 99%
“…is by no means a caricature, but a relatively accurate portrait of how studies in evolutionary biology are at present conducted and reported. The vast majority of investigations in our field still follow the traditional NHST scheme, despite ample exposure of its problems for about a century (Amrhein et al, 2017;Berkson, 1938;Boring, 1919;Gigerenzer, 2018;Greenland, 2017;Hurlbert & Lombardi, 2009;Johnson, 1999;Mayo, 2018;McShane et al, 2019;Oakes, 1986;Rozeboom, 1960;Szucs & Ioannidis, 2017;Yates, 1951;Ziliak & McCloskey, 2008), and despite broad agreement within the community of statisticians that the current state of NHST usage is damaging to science (Amrhein et al, 2019a;Benjamin et al, 2018;Seibold et al, 2021;Wasserstein & Lazar, 2016;Wasserstein et al, 2019).…”
Section: How Widely Are the Above Miscon Cep Ti On S Recog Nized In O...mentioning
confidence: 99%
“…is by no means a caricature, but a relatively accurate portrait of how studies in evolutionary biology are at present conducted and reported. The vast majority of investigations in our field still follow the traditional NHST scheme, despite ample exposure of its problems for about a century (Amrhein et al, 2017;Berkson, 1938;Boring, 1919;Gigerenzer, 2018;Greenland, 2017;Hurlbert & Lombardi, 2009;Johnson, 1999;Mayo, 2018;McShane et al, 2019;Oakes, 1986;Rozeboom, 1960;Szucs & Ioannidis, 2017;Yates, 1951;Ziliak & McCloskey, 2008), and despite broad agreement within the community of statisticians that the current state of NHST usage is damaging to science (Amrhein et al, 2019a;Benjamin et al, 2018;Seibold et al, 2021;Wasserstein et al, 2016Wasserstein et al, , 2019.…”
Section: How Widely Are the Above Misconceptions Recognized In Our Li...mentioning
confidence: 99%
“…Isolated statisticians in the academic health sciences occupy a non‐traditional role as they are non‐clinicians in a medical environment, focused on team‐science research instead of independent methodological research, with less influence and generally in positions perceived as less prestigious (e.g., staff or non‐tenure track versus tenure‐track faculty). Among other contributions, statisticians also bring a commitment to rigor and reproducibility that benefits all research (Satagopan & Mazumdar, 2021; Seibold et al, 2021). The statisticians' efforts to improve the rigor and reproducibility of science more broadly with stronger study designs and enhanced data collection and analyses can potentially cause friction within a team due to a perception of divided loyalties.…”
Section: Specific Challengesmentioning
confidence: 99%